Analisis Implementasi PDCA dalam Perspektif Manajemen Mutu Terpadu di MAN 1 Boyolali - Diah Ihsaniati Fatimah; Nofa Zahra Febrianti; Fetty Ernawati (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to analyze the implementation of the PDCA cycle from the perspective of Total Quality Management (TQM) at MAN 1 Boyolali. This research is motivated by the importance of continuous quality improvement in education to create effective and high-quality educational services that meet the needs of students and society. The implementation of PDCA is considered one of the management strategies that can assist educational institutions in conducting systematic and continuous planning, implementation, evaluation, and improvement processes. This study employed a qualitative design. Data were collected through observation, interviews, and documentation involving the principal, teachers, educational staff, and school quality management documents. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results indicate that the implementation of PDCA at MAN 1 Boyolali has been carried out systematically in various aspects of educational management. In the plan stage, the madrasah collaboratively formulates work programs, quality targets, and learning plans. The do stage is implemented through learning activities, school programs, and educational services based on predetermined standards. The check stage is conducted through supervision, evaluation meetings, activity monitoring, and assessment of students’ learning outcomes. Furthermore, the action stage is realized through follow-up improvements based on evaluation results to enhance the quality of educational services. The implementation of PDCA from the perspective of TQM has positively contributed to improving learning quality, teacher professionalism, school quality culture, and stakeholder satisfaction. However, several challenges remain, including limited human resources and uneven understanding within the madrasah environment.